(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
The objective of the present investigation was to analyze thepattern of Genotype x Environment (G x E) interaction for grain yield ofsixteen rice genotypes using Additive Main effects And MultiplicativeInteraction (AMMI) model. Genotypes were grown at two locations (Ed-duim and Kosti, White Nile State, Sudan) for two years. Main effects dueto environment (E), genotypes (G) and GxE interaction (GEI) weresignificant (p<0.01), with highest variation (63.3%) accounted for byenvironmental effects. The first Interaction Principal Component Axes(IPCA 1) was significant (p<0.01) and contributed 72.4% of the total GEI.The biplot was identified genotypes and testing environments thatexhibited major sources of GE interaction as well as those that werestable. YUNLU 33 was identified as the best genotype (higher yieldingand stable)